Private peaceful - Morpurgo, Michael (London : Collins, 2003)
When Thomas Peaceful's older brother is forced to join the British Army, Thomas decides to sign up as well, allthough he is only fourteen years old, to prove himself to his countru, his family, his childhood love, Molly, and himself.
Keywords: Poverty -- Fiction; Single-parent families -- Fiction; Soldiers -- Fiction; World War I -- 1914-1918 -- Fiction